Pendidikan Kesehatan SADARI (PERI) Meningkatkan Pengetahuan Remaja Putri: Studi Kuantitatif: BSE Health Education (PERI) Increases Knowledge Adolescent Girls: A Quantitative Study - Okta Rinarta, Vella; Mardiyaningsih, Eko (Indonesian Journal of Midwifery (IJM), 2025)
Breast cancer is one of the leading causes of death among women worldwide. Early detection through breast self-examination (BSE) is an effective preventive measure. However, knowledge about BSE among adolescent girls remains low. Health education through video media is considered an efficient method to improve adolescents' understanding of breast health. To examine the effectiveness of BSE health education (PERI) using video media in increasing knowledge among female students. This study employed a quantitative method with a quasi-experimental design using one group pre-test and post-test design. The sample consisted of 60 female students from grades 7 to 9 selected through total sampling. Data were collected using a validated and reliable BSE knowledge questionnaire. Data analysis was conducted using the Paired T-test with a 5% significance level. Most respondents were 14 years old (38.3%), and 93% had never received any information about BSE. The Paired T-test showed a significant difference between pre-test and post-test scores (p = 0.000), with the average knowledge score increasing from 11.60 to 17.77 after the video-based intervention, indicating a mean difference of 6.17. Health education on BSE through video media effectively improves adolescent girls' knowledge of early breast cancer detection. Visual and auditory educational approaches such as videos can serve as strategic alternatives in adolescent reproductive health promotion, especially in increasing awareness and practice of BSE from an early age.   Abstrak Kanker payudara merupakan salah satu penyebab utama kematian pada perempuan di dunia. Deteksi dini melalui pemeriksaan payudara sendiri (SADARI) menjadi langkah preventif yang efektif. Namun, pengetahuan remaja putri tentang SADARI masih tergolong rendah. Edukasi melalui media video dipandang sebagai metode yang efisien untuk meningkatkan pemahaman remaja mengenai kesehatan payudara. Menguji efektivitas pendidikan kesehatan SADARI (PERI) terhadap peningkatan pengetahuan remaja putri. Penelitian ini merupakan studi kuantitatif dengan desain quasi experimental menggunakan one group pre-test and post-test design. Sampel berjumlah 60 siswi kelas 7 hingga 9 yang dipilih melalui teknik total sampling. Pengumpulan data dilakukan dengan kuesioner pengetahuan SADARI yang telah diuji validitas dan reliabilitasnya. Analisis data menggunakan uji Paired T-test dengan tingkat signifikansi 5%. Mayoritas responden berusia 14 tahun (38,3%) dan 93% belum pernah memperoleh informasi tentang SADARI. Hasil uji Paired T-test menunjukkan adanya perbedaan yang signifikan antara nilai pre-test dan post-test (p = 0,000), dengan rata-rata skor pengetahuan meningkat dari 11,60 menjadi 17,77 setelah intervensi video edukatif, dengan selisih mean 6,17. Intervensi pendidikan kesehatan SADARI melalui media video terbukti efektif dalam meningkatkan pengetahuan remaja putri tentang deteksi dini kanker payudara. Edukasi visual dan auditori seperti video dapat dijadikan alternatif strategis dalam promosi kesehatan reproduksi remaja, khususnya dalam meningkatkan kesadaran dan praktik SADARI sejak usia dini.